Republic of Mozambique : Joint Staff Advisory Note of the Annual Progress Report on Implementation of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Joint Staff Advisory Note provides advice on the PARPA (the Mozambican Poverty Reduction Strategy Paper) implementation in 2004 and its main goals for 2005. It draws mainly on the government's Annual Progress Report (APR) on PARPA implementation for 2004, and the 2005 Economic and Social Plan (PES). The IMF staff agrees with the APR view that a number of the Millennium Development Goals are within Mozambique's reach but that, to achieve others, Mozambique will require the help of the international community to make further progress and attract more investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet